Development E-Module Flipbook-Based in Basic Programming Subjects in Vocational High School: Pengembangan E-Modul Berbasis Flipbook Pada Mata Pelajaran Pemrograman Dasar di SMK - Muhammad Surya Abadi Abd Hakam; Rahmania Sri Untari (Universitas Muhammadiyah Sidoarjo, 2021)
The use of learning media flipbook as learning material for students is a solution to better understand the material when the learning process takes place. This study aims to determine the development and feasibility of a-based E-Modul flipbook in basic programming subjects at SMK YAPALIS Krian. This type of research is Research and Development (R&D) using the development model Analysis, Design, Development, Implementation, Evaluation (ADDIE). The feasibility test was carried out by material experts and media experts and the results of the students' responses, the results of the validity of this study obtained a percentage of 95% with the